Solve ln(2x-3) = 1

eln(2x-3) = e1
2x-3 = e
x = (e+3)/2

Answered by Jonathan C. Maths tutor

4898 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

What is the natural logarithm?


Solve the equation x^6 + 26x^3 − 27 = 0


find the value of dy/dx at the point (1,1) of the equation e^(2x)ln(y)=x+y-2


Express cos(2x) in the form acos^2(x) + b, where a and b are constants.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences